2010
DOI: 10.1177/0022002710374715
|View full text |Cite
|
Sign up to set email alerts
|

Aiding and Abetting: Human Rights INGOs and Domestic Protest

Abstract: This article studies the effects of human rights international nongovernmental organizations (INGOs) on domestic antigovernment protest. Unlike mainstream scholarship, the authors argue that human rights INGOs are not simply the magic bullet in orchestrating nonviolent protests; different types of human rights INGO activity have varying effects on protest. Moreover, some human rights INGO activities may lead to higher levels of violent protest. The empirical tests use new data on the activities of over 400 hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
130
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(135 citation statements)
references
References 51 publications
3
130
0
2
Order By: Relevance
“…Also, the human rights network may condition the effect of interventions (such as "naming and shaming") meant to improve human rights practices (Keck and Sikkink, 1998;Risse and Sikkink, 1999;Murdie and Bhasin, 2011). Interventions aimed at preventing torture may be more effective when fewer violations of other rights are present, and ineffective when human rights are broadly violated.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the human rights network may condition the effect of interventions (such as "naming and shaming") meant to improve human rights practices (Keck and Sikkink, 1998;Risse and Sikkink, 1999;Murdie and Bhasin, 2011). Interventions aimed at preventing torture may be more effective when fewer violations of other rights are present, and ineffective when human rights are broadly violated.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, as previous research has found a significant positive relationship between violent protest and non-violent protest, we control for the occurrence of the violent protest in each model. 71 As our theory explicitly acknowledges the degree to which many outcomes and events cluster in geographic space as well as time, we control for temporal and spatial autocorrelation in all models. Our control for temporal autocorrelation is a one-year lag of the dependent variable.…”
Section: Control Variables and Model Specificationmentioning
confidence: 99%
“…In the secular arena of large donors and UN peacebuilding efforts, efforts to promote human rights and peace "have historically proceeded on separate tracks" (Sharp 2013: 195). Secular human rights scholarship tends to focus more on the role of human rights NGOs in promoting or ameliorating (armed) conflict or protests, rather than a discussion of "peace" per se (Murdie and Bhasin 2011), or focuses on negative peace between actors; for example, weighing the costs and benefits of human rights prosecution after a civil war (Anonymous 1996;Hayden 2004;Akhavan 2009). In contrast, religious organizations tend to espouse a more holistic view of "peace" that includes addressing systemic injustice and restorative processes of conflict resolution (AFSC 2012; MCC).…”
Section: Religious Vs Secular Approaches To Human Rightsmentioning
confidence: 99%